Magnetic Field-Enhancing Photocatalytic Reaction in Micro Optofluidic Chip Reactor - Hung Ji Huang; Yen Han Wang; Yuan-Fong Chou Chau; Hai-Pang Chiang; Jeffrey Chi-Sheng Wu (Nanoscale Research Letters, 2019)
Abstract A small external magnetic field (100–1000 Oe) was demonstrated to enhance the photocatalytic degradation of methyl orange (MO) using TiO2 NPs in micro optofluidic chip (MOFC) reactors. The rectangular shape of the fluidic channel and TiO2 deposited only onto the lower glass substrate leads to a selectively enhancing photocatalytic reactions by magnetic field in specific directions. Utilizing ethyl alcohol as a scavenger presented the difference between generated hot-hole (hVB+) and hot-electron (eCB−) pathways of photocatalytic reactions. Effects of dissolved oxygen (DO) and hydroxyl ions (OH−) are all demonstrated in a magnetic field-enhancing photocatalytic reaction. The experimental results demonstrate great potential for practical applications utilizing low-price fixed magnets in the field of green chemistry.